2014
DOI: 10.1155/2014/159784
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Investigation of First Cervical Vertebrae Morphology and Hyoid Position in Young Adults with Different Sagittal Skeletal Patterns

Abstract: The aim of this retrospective study was to examine hyoid bone position and C1 (atlas) morphology in males and females and analyze these parameters with respect to different sagittal skeletal patterns via cephalometry, with the goal of identifying cephalometric norms. Lateral cephalometric radiographs from 120 individuals (average age: 21.1 ± 2.9 years) were classified according to their ANB angle (Class I, II, or III) and used to assess 14 parameters. Class I and II patients showed significant differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(42 reference statements)
0
3
1
1
Order By: Relevance
“…The present study revealed that the relationship among the ANB angle and the hyoid bone position was reversely correlated in healthy patients which was a disagreement with different studies like Abu Alhaija et al [33] and Arslan et al [12] . It also showed no significant statistical difference between different facial morphologies or growth patterns and the position of the hyoid bone and hence proving wrong in the basis of Jarabak's ratio which is one of the oldest and commonest used ratios for growth patterns and facial morphologies.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study revealed that the relationship among the ANB angle and the hyoid bone position was reversely correlated in healthy patients which was a disagreement with different studies like Abu Alhaija et al [33] and Arslan et al [12] . It also showed no significant statistical difference between different facial morphologies or growth patterns and the position of the hyoid bone and hence proving wrong in the basis of Jarabak's ratio which is one of the oldest and commonest used ratios for growth patterns and facial morphologies.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that the hyoid bone position differs in each type of malocclusion. It is positioned inferiorly in Class I and Class II malocclusion, 37,38 and superiorly in Class III malocclusion. 39 In the present study, the hyoid bone was found to be more superior to the mandible in the cases as compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…It is due to the fact that the majority of controls had Class I and II malocclusion, which is consistent with what has been previously reported. 37,38 The majority of cases, however, had Class II malocclusion, but the hyoid bone was still located superior to the mandible; this can be explained by the fact that although the dominant malocclusion type was Class II, the associated LFH and VAL were reduced, which means that there was less space for the tongue, resulting in the stretching of the associated soft tissues which are connected to the epiglottis, thereby elevating the hyoid bone more superiorly.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados fueron similares a un estudio efectuado por Khanna et (25,26), revelan que el hueso hioides mantiene una posición y orientación constante en individuos con diferentes patrones esqueletales. Sin embargo, en dichas investigaciones utilizaron muestras pequeñas de estudio lo cual disminuye su confiabilidad.…”
Section: Discussionunclassified